INTRODUCTION OF ADVANCED PEDAGOGY AND INFORMATION COMMUNICATION TECHNOLOGIES INTO THE PRESCHOOL EDUCATION SYSTEM (European Journal of Interdisciplinary Research and Development, 2025)
This article gives ways to introduce advanced pedagogy and information communication technologies into the preschool education system. Information about information communication technologies introduced in the preschool education system today.